THE RELATIONSHIP OF SOCIAL SUPPORT WITH THE DEGREE OF NAUSEA AND VOMITING IN PREGNANCY - Cempaka Yudithia Junandar; Ivon Diah Wittiarika; Budi Utomo; Ernawati Ernawati (UNIVERSITAS AIRLANGGA, 2020)
Abstract Background : At the beginning of a pregnancy the mother experiences various processes of transition or adaptation regarding changes in herself, so that she really needs support from her environment. Lack of social support can worsen the physiological complaints of pregnant women including Nausea and Vomiting in Pregnancy (NVP). Complaints of nausea and vomiting can affect the mother in carrying out daily activities, affect the mother's social situation with the environment and cause stress. Therefore, it is important to research the relationship between social support and the degree of nausea and vomiting in first and second-trimester pregnant women. Method : This research method is observational analytic with cross sectional research design. Sampling used the total sampling method with the criteria of pregnant women who had complaints of nausea and vomiting. Collecting data using primary data using a 24-hour PUQE questionnaire that measures the duration and frequency of nausea and vomiting and the MSPSS questionnaire measuring social support. The data collected were analyzed using the Spearman test (p<0.15). Results : Out of 47 respondents, 34 pregnant women (72.3%) received high social support. Besides that, 24 out of 47 respondents (51.1%) experienced moderate degree of NVP. In this study, there were no respondents who experienced severe degree of NVP. Spearman test analysis results obtained p= 0.833 or p>0.15. Conclusion : There is no relationship between social support with NVP in first and second trimester of pregnancy.